Rancang Bangun Alat Pengembalian Buku Perpustakaan Secara Mandiri Berbasis Single Board Computer - Akbar, Nazri Ilhamzah; Rahmadya, Budi; Eka Putri, Rahmi (CHIPSET, 2023)
the process of borrowing and returning library books usually requires a librarian to go through this process, of course this requirement can cause delays in returning books due to library holidays and the difference in free hours from the library and library members. so this research aims to make it easy for library members to be able to return books independently using a storage box that can be done by the system. in this book return box using a raspberry pi 3b+ as a data processing center and using the pi camera to capture the book cover made on the book return box. the security system in this return box uses a selenoid door lock as an automatic door lock which will be routed by a relay and uses rfid as the identity of books, members and librarians. in this study the system can store and return books using the K-Nearest Neighbor (KNN) method with an accuracy of 95% with a processing time of 6.9s